Considerations on the Improved Integration of Medical Guidelines into Routine Clinical Practice – a Review and Concept Proposal - Beckmann, M. W.; Schlieter, H.; Richter, P.; Wesselmann, S. (Geburtshilfe und Frauenheilkunde, 2016)
Medical guidelines have become established as the standard for the comprehensive synopsis of all available information (scientific trials, expert opinion) on diagnosis and treatment recommendations. The transfer of guidelines to clinical practice and subsequent monitoring has however proven difficult. In particular the potential interaction between guideline developers and guideline users has not been fully utilised. This review article analyses the status quo and existing methodological and technical information solutions supporting the guideline life cycle. It is shown that there are numerous innovative developments that in isolation do not provide comprehensive support. The vision of the “Living Guidelines 2.0” is therefore presented. This outlines the merging of guideline development and implementation on the basis of clinical pathways and guideline-based quality control, and building on this, the generation of information for guideline development and research.
Keywords: medical guidelines; evidence based medicine; clinical pathways; quality management